Effectiveness of Cooperative Learning Model For Enhancing Capability of Investigation tipe group Resolution on Student Mathematical Hight School - S. Supratman; Akbar Nasrum (Universitas Sembilanbelas November Kolaka, 2018)
TThe purpose of this study are: (1) To determine the ability of mathematical problem solving class X SMA Negeri 1 Wundulako taught using cooperative learning model Group Investigation. (2)To determine the ability of mathematical problem solving class X SMA Negeri 1 Wundulakoyang taught using conventional learning model in teaching trigonometry. (3) To determine whether the mathematical problem solving ability of students taught bycooperative learning model of Group Investigationbetter than mathematics problem solving ability of students taught by conventional learning models in Class 1 Wundulako State XSMA in teaching trigonometry. This type of research used experimental method. The population in this study were all students of class X are scattered in seven classes in parallel with the number of 155 people. Sampling was conducted using random cluster sampling technique. In this study as a sample taken two classes of the population that there is a class X2 as an experimental class and class X4 as the control class. From the results of data analysis showed that: (1) average math problem solving ability X2 grade students taught using cooperative learning model type investigative groups (Group Investigation), which consists of 19 students showed minimum value maximum value 96.00 72.00 , the average (mean)87.0526, median88.00 and mode86.00, With a variance40.608And standard deviation 6.37246, (2 average math problem solving ability X4 grade students taught using conventional learning model which consists of 22 students showed 68.00 minimum value, maximum value 96, 00 average (mean)82.3636, median82,00, and mode82.00, With a variance58.147And standard deviation7.62543, (3) the results of t-test analysis using independent samples t-test obtained t =2.116 on the significant 0,005 Î± = 0.05then H0 is rejected and H1 accepted. With the rejection of H0, it can be concluded that the increase in mathematical problem solving ability of students taught using cooperative learning model type investigative groups (Group Investigation) is better than math problem solving ability of students taught using conventional learning models.